Translocation of a parthenogenesis gene candidate to an alternate carrier chromosome in apomictic Brachiaria humidicola - Worthington, Margaret; Ebina, Masumi; Yamanaka, Naoki; Heffelfinger, Christopher; Quintero, Constanza; Zapata, Yeny Patricia; Pérez, Juan Guillermo; Selvaraj, Michael Gomez; Ishitani, Manabu; Duitama, Jorge; Hoz, Juan Fernando de la; Rao, Idupulapati M.; et al. (Springer, 2019)
The apomictic reproductive mode of Brachiaria (syn. Urochloa) forage species allows breeders to faithfully propagate heterozygous genotypes through seed over multiple generations. In Brachiaria, reproductive mode segregates as single dominant locus, the apospory-specific genomic region (ASGR). The AGSR has been mapped to an area of reduced recombination on Brachiaria decumbens chromosome 5. A primer pair designed within ASGR-BABY BOOM-like (BBML), the candidate gene for the parthenogenesis component of apomixis in Pennisetum squamulatum, was diagnostic for reproductive mode in the closely related species B. ruziziensis, B. brizantha, and B. decumbens. In this study, we used a mapping population of the distantly related commercial species B. humidicola to map the ASGR and test for conservation of ASGR-BBML sequences across Brachiaria species.